FINKI scholar, a publications database for Faculty of Computer Science and Engineering scholars - Risteska Stojkoska, Biljana; Gjorshevski, Hristijan; Mitreva, Elizabeta (Telecommunications Society, Belgrade Academic Mind, Belgrade, 2021)
The aim of this paper is to develop a web application where scholars of the Faculty of Computer Science and Engineering (FINKI) at the University of Ss. Cyril and Methodius can display and share their projects and publications. Visitors can view, search through, and filter the authors, projects and publications that can be added and edited by the administrators via the administrator panel. In this paper, we first explain the type of system we are building and go through similar existing systems explaining how they work and what they offer. Then, we go through the programming languages and technologies we decided to use to develop this web application. After that, the development phase follows, where we describe each of the features we implemented. In The Final Product section we finally show images where you can see how the web application works and what it looks like. We finish the paper with a conclusion, briefly summarizing what we have achieved.
Keywords: application, FINKI, Laravel, MySQL, publications, PHP, scholars, web